2018
DOI: 10.1111/ene.13768
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult‐onset cerebellar ataxia in Italy

Abstract: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…We found that p.Ala510Val homozygotes patients have a milder phenotype than compound heterozygotes, including a lower frequency of ptosis, bladder disorders, pyramidal signs (Babinski), and sensory signs . Unlike van Gassen and colleagues, we did not find a correlation between genotype and form of the disease, given that the same variant may cause pure and complex forms with a large phenotypic heterogeneity.…”
Section: Discussioncontrasting
confidence: 85%
“…We found that p.Ala510Val homozygotes patients have a milder phenotype than compound heterozygotes, including a lower frequency of ptosis, bladder disorders, pyramidal signs (Babinski), and sensory signs . Unlike van Gassen and colleagues, we did not find a correlation between genotype and form of the disease, given that the same variant may cause pure and complex forms with a large phenotypic heterogeneity.…”
Section: Discussioncontrasting
confidence: 85%
“…Next, we tested the human SPG7_ del fibroblasts together with four SPG7 missense mutant cells [59] ( Fig. 1 G ), as well as fibroblasts deriving from non-SPG7 forms of HSP, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the recessive forms, our study confirmed that SPG11 is one of the most common AR HSP genes: indeed, together with those in CYP7B1 /SPG5, DDHD2 /SPG54, and FA2H /SPG35, mutations in SPG11 account for half of all AR cases. Finally, the relatively low frequency of mutations in SPG7 might be related to their study in a concurrent “ataxia-associated” NGS panel (54).…”
Section: Discussionmentioning
confidence: 99%